Utilizing dense magnetotelluric array to analyze deep seismogenic environment in the Huaibei plain fold belt - Li, Pengfei; Cai, Juntao; Lu, Shuo; Chen, Xiaobin; Yang, Yuanyuan; Shu, Peng; Pan, Haobo; Zheng, Yingping; Fang, Lianghao (Frontiers in Earth Science, 2025)
The Huaibei Plain Fold Belt, located on the southeastern margin of the North China Plate, lies adjacent to the Tancheng-Lujiang fault zone—one of the most active fault zones in eastern China—characterized by complex tectonic activity. Using a 3D dense magnetotelluric (MT) array, we obtained high-quality MT data through fine time-series processing technology. Dimensionality and structural characteristics were analyzed using phase tensor analysis and statistical imaging of the impedance tensor. A fine and reliable 3D resistivity structure was constructed through nonlinear inversion, combining impedance data with a multiple iterative reconstruction technique. The results reveal that the high-resistivity and low-resistivity areas at shallow depths correspond to the Xuhuai arcuate tectonic structure and the Suzhou-Haogou Basin, respectively, with prominent low-resistivity anomalies present in the middle and lower crust. Beneath the Suzhou-Haogou Basin, blind low-resistivity faults are embedded within high-resistivity media and appear to be connected to deeper low-resistivity anomalies. These low-resistivity features are interpreted as the result of intense tectonic deformation and the presence of crustal fluids. There is no evidence of mantle-derived thermal upwelling, suggesting that deep mantle processes have limited influence on current tectonic deformation. Our findings indicate that the Huaibei Plain Fold Belt hosts a deep structural setting capable of generating strong earthquakes, with deformation primarily driven by horizontal tectonic forces. However, the underlying mechanism driving this deformation requires further investigation.